The effect of tendon excursion velocity on longitudinal median nerve displacement: Differences between carpal tunnel syndrome patients and controls. Issue 4 (17th February 2015) - Filius, Anika; Thoreson, Andrew R.; Wang, Yuexiang; Passe, Sandra M.; Zhao, Chunfeng; An, Kai‐Nan; Amadio, Peter C.
ABSTRACT: The subsynovial connective tissue (SSCT) is a viscoelastic structure connecting the median nerve (MN) and the flexor tendons in the carpal tunnel. Increased strain rates increases stiffness in viscoelastic tissues, and thereby its capacity to transfer shear load. Therefore, tendon excursion velocity may impact the MN displacement. In carpal tunnel syndrome (CTS) the SSCT is fibrotic and may be ruptured, and this may affect MN motion. In this study, ultrasonography was performed on 14 wrists of healthy controls and 25 wrists of CTS patients during controlled finger motions performed at three different velocities. Longitudinal MN and tendon excursion were assessed using a custom speckle tracking algorithm and compared across the three different velocities. CTS patients exhibited significantly less MN motion than controls ( p  ≤ 0.002). While in general, MN displacement increased with increasing tendon excursion velocity ( p  ≤ 0.031). These findings are consistent with current knowledge of SSCT mechanics in CTS, in which in some patients the fibrotic SSCT appears to have ruptured from the tendon surface. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:483–487, 2015.